SEMIOTIKA POSITIONING POLITIK KANDIDAT DALAM VIDEO DEBAT KANDIDAT PILKADA JAKARTA 2017 - Iskandar Iskandar; Sulvinajayanti Sulvinajayanti; Nahrul Hayat (KOMUNIDA : Media Komunikasi dan Dakwah, 2017)
This research is motivated by the rampant phenomenon of regional election campaign (Pilkada) through candidate debate which is broadcasted directly by television mass media. Candidate debate is a model of political communication that is fairly newly dipratekkan in the election of regional heads in Indonesia. Despite the public's attention, the candidate debate in the communication perspective has not been widely seen as the subject of communiqué research. The research methodology used qualitative descriptive approach with semiotic analysis method. This approach is chosen because it is able to reveal various information by way of description in the form of verbal and nonverbal messages of a text in a special context that melatarinya. Data were collected through observation techniques, documentary studios and libraries as well as interviews of expert informants. The data were then analyzed using semiotics method developed by Roland Barthes consisting of two marking levels. The conclusion of the research results indicate that each candidate builds political positioning to form the image and the good impression in the mind of the audience. The comparison of the political positioning of the two candidate pairs is that Ahok-Djarot is a candidate for the regional head that is firm and straightforward, experienced, and secular with the nature of top-down policy making. While Anis-Sandi is a decent candidate for regional head and nurturing, pro people, and tend to be religious with the nature of decision making bottop-up.